Safety and efficacy of Natuphos® E (6‐phytase) as a feed additive for avian and porcine species. (14th November 2017) - ,; Rychen, Guido; Aquilina, Gabriele; Azimonti, Giovanna; Bampidis, Vasileios; Bastos, Maria de Lourdes; Bories, Georges; Chesson, Andrew; Flachowsky, Gerhard; Gropp, Jürgen; Kolar, Boris; Kouba, Maryline; et al.
Abstract: Natuphos ® E is a feed additive that contains a 6‐phytase available in powder, granulated and liquid forms which is intended to be used as a feed additive for avian and porcine species. The production strain of the phytase present in the product is a genetically modified strain of Aspergillus niger . The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that the genetic modification of the production strain does not give rise to safety concerns. The production strain and its DNA were not detected in the concentrate used to formulate the products. Based on the tolerance studies provided, the Panel concluded that the additive is safe for the target species under the conditions of use with a wide margin of safety. The Panel also concluded that the use of the product as a feed additive does not give rise to concerns for consumers. Evidence was provided showing that the additive is not toxic by inhalation or irritant for skin or eyes, however, it should be regarded as a dermal sensitiser and a potential respiratory sensitiser. The use of the additive as a feed additive poses no risks to the environment. Based on the efficacy studies provided, the Panel concluded that the additive has the potential to be efficacious in chickens for fattening, turkeys for fattening, piglets, pigs for fattening and sows. These conclusions were extended to chickens reared for laying, turkeys reared for breeding and extrapolated to minor poultry species and other avian species for fattening and to the point of lay and to minor porcine species. The Panel considered that there was insufficient information to conclude on the efficacy in laying hens.